Eva Besnyö Pictures the Dutch. Modernism and Mass Culture at Sea in the Interwar Period - Remco Ensel (BMGN: Low Countries Historical Review, 2018)
In 1938, the Hungarian-Dutch photographer Eva Besnyö contributed with a stylish photo wall to the interior decoration of the passenger ship Nieuw Amsterdam. Besnyö’s photography was part of a unique collaboration between the shipping company and more than sixty artists. In mass media and manifestations the ocean liner was presented as one huge floating signifier of national grandeur and tradition. The photo wall fitted perfectly in this narrative but this was precisely why Besnyö had her doubts. In this article I seek to find out how the photographer managed to produce the wall working within the limits of her penchant for modernism and the demands of the assignment. I argue that the poetic quality of the composition lies in the way in which the photographer as bricoleur from the debris of available images created a visualised myth of the nation, as expounded by Claude Lévi-Strauss. Both the photo wall and the ship’s interior as Gesamtkunstwerk can be understood as utopian attempts to reconcile modernism and mass culture.